Banking Supervisors and External Auditors : Building a Constructive Relationship - World Bank Group (World Bank, Vienna, 2016)
The 2008 financial crisis highlighted weaknesses in the risk management, control and governance processes of banks as well as in their statutory audit and financial supervision. This led to increased scrutiny of the respective roles and interactions of banking supervisors and external auditors who are key contributors to market discipline. Auditors ensure that financial information is transparent and reliable while supervisors provide confidence in the financial systems. Both supervisors and auditors allow market players to make informed decisions and contribute to financial stability. Since 2008, regulators and lawmakers have strived to address the shortcomings identified during the crisis by taking various initiatives to reform the international financial architecture In particular, a 2014 Basel Committee on Banking Supervision paper explored the interaction between supervisors and external auditors and linked their enhanced relationships with improved audit quality of banks’ financial statements and effective banking supervision. This report presents the findings of the survey conducted by the World Bank Centre for Financial Reporting Reform (CFRR) – Financial supervisors and external auditors: building a constructive relationship. The survey was sent to supervisors from the European Union and other countries in Eastern Europe, South Eastern Europe and the South Caucasus to explore practices that make better use of information provided by external auditors and influence the audit quality of banks’ financial statements. The report was developed after several workshop discussions amongst senior staff from central banks and banking regulatory agencies, who recognized the importance of an effective relationship to assist both supervisors and auditors in discharging their duties.